2010
DOI: 10.1177/1352458510364992
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological evidence that axonal loss underlies disability in progressive multiple sclerosis

Abstract: Growing evidence suggests that axonal degeneration rather than demyelination is the pathological substrate underlying chronic, irreversible disability in multiple sclerosis. However, direct evidence linking clinical disability measured in vivo with corresponding post-mortem measures of axonal pathology is lacking. Our objective in this study was to investigate the relationship between motor disability accumulated by patients with multiple sclerosis during life and the degree of axonal loss observed in their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 44 publications
2
114
2
2
Order By: Relevance
“…Spinal cord pathology is an important determinant of permanent neurological disability with cardinal characteristics being inflammatory demyelination, synaptic, neuronal and axonal loss 6, 7, 8, 9, 10, 11. The precise nature of how these pathological alterations impact clinical phenotypes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord pathology is an important determinant of permanent neurological disability with cardinal characteristics being inflammatory demyelination, synaptic, neuronal and axonal loss 6, 7, 8, 9, 10, 11. The precise nature of how these pathological alterations impact clinical phenotypes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Demyelination is considered the most characteristic histopathological feature of MS. Recent studies, however, revealed that MS is also a neurodegenerative disease with early neuroaxonal damage [1][2][3] .…”
Section: Introduction Optic Neuritis As a Model For Tracking Tissue Dmentioning
confidence: 99%
“…Psychological and psychiatric comorbidities like depression, anxiety and social isolation are often reported in patients with this disease 1 . Demyelination can occur in several areas of the central nervous system and neurological disability may be the result of relapsing or progressive damage to axonal myelin 2 . Empathy is a complex state of mind that depends on the skill to project oneself into another person's situation.…”
mentioning
confidence: 99%